Knowledge management and key factors for organizational success in the perspective of the 21st Century - Hernández García de Velazco, Judith J.; Ravina Ripoll, Rafael; Chumaceiro Hernandez, Ana Cecilia; Tobar Pesantez, Luis Bayardo (Revista Venezolana de Gerencia, 2021)
This paper will analyze knowledge management trends in organizations framed in the most up-to-date currents in administration in order to explain the knowledge-based vision, developed by multi-dimensional strategies in value creation. Furthermore, considering the various critical processes from the strategic alliances and the dynamic capabilities that determine it. In an analytical, bibliographic-documentary approach, study categories are defined to interpret and contrast how knowledge continues to be a comparative advantage, demonstrated in its conceptual deconstruction, where theoretical discussions are generated. The same advantage point to new conceptions extracted from its applicative composition in the 21st century organizations, which implies various human and process adaptations. It is concluded that knowledge management and dynamic capacities, and strategic alliances are essential for organizational success and social welfare.